Pengaruh Mesin Pencari Google sebagai Sumber Belajar terhadap Pengetahuan Kewarganegaraan Peserta Didik pada Mata Pelajaran PPKn - Oki Purwanti; Ratna Sari Dewi; Reza Mauldy Raharja (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
The purpose of this research is to see the relations between influence of the google search engine as a learning source on citizenship knowledge in Daarussalam Sindang Jaya Senior High School (SMA) in Tangerang Regency. The approach used in this study is correlational quantitative. The population in this study were class XI in the 2022/2023 academic year. In this study, the Simple Random Sampling technique was used as a technique to obtain research samples. After conducting the research, it was found that the Google Search Engine as a Learning Resource was in the sufficient or moderate category with details of the frequency of 74% which, if converted, were as many as 40 people out of 54 students. For Student Citizenship Knowledge (Variable Y) is in the sufficient or moderate category with a frequency of 70% with a total of 38 students out of 54 students. With the level of influence based on the results of the correlation analysis shows that the Fcount value = 22.879, while the significance level is 0.000 <0.05. Thus it is concluded that the regression model can predict the independent variable (X). For this reason, it is known that there is the influence of the Google search engine which is used as a source of learning about citizenship knowledge. From the results of testing using the Simple Linear Regression technique, it is known that the correlation value or relationship (R) is 0.553, and the coefficient of determination (R Square) is 0.306 which means that the effect on variable X on variable Y is 30.6%.